Anomie, Social Change and Crime - Bernburg, Jon Gunnar (British Journal of Criminology, 2002)
The last decade has seen a revived interest in using anomie theory in crime and deviance research. The present paper contributes to this development by offering an examination of a particular extension of anomie theory, namely, Messner and Rosenfeld's Institutional-Anomie theory. Explicating Institutional-Anomie theory relative to the sociologies of Durkheim, Merton and Polanyi, I find that this theory goes beyond Merton by using a strain of thought that is critical of liberal society. By bringing in the notion of the disembedded market economy, a central notion in the institutionalism of Polanyi and Durkheim, this theory links crime, anomie, and contemporary social change. I also discuss some of the limitations of linking crime with societal level processes in a Durkheimian rather than Mertonian manner.
Sociology; Criminology
Keywords: DURKHEIM; Emile; MERTON; Robert; anomie; crime; criminology; disembeddedness